Does sports make people happier, or do happy people more sports? - Bruno S. Frey; Anthony Gullo (Center for Research in Economics, Management and the Arts (CREMA), 2021)
Between sports and happiness. Using longitudinal data from the German Socio- Economic Panel (GSOEP), we find a positive correlation between sports participation and reported life satisfaction. This relationship is stronger at younger and older ages than in middle age, and for people in bad health compared to those in average health. We further provide evidence for both causal directions. It turns out that the causal impact of engaging in sports on happiness is about four times higher than the effect of happiness on engaging in sports.
Keywords: 330; happiness; life satisfaction; well-being; sports; causality